Strategi Koping Wanita Dalam Menghadapi Konflik Peran Ganda - Saputro, Dhanang Dwi, Aad Satria Permadi, S.Psi, MA (2016)
Woman employed a common phenomenon we are witnessing today. The development of industry, the more labor is needed including woman. When in Indonesian culture, the role of women in the household has the responsibility for its own which is to take care of any other use the house and family members in it. Th role of it will be attached to lady when has become a housewife. Women are obliged to take care of the house, husband and also thie children(s). Responsibility that were significant that, then there was some of them choose to work. There are many things that push woman choose to work, because of bored while at home, increase economy family, use their science from college and many other motivation it has. Here researcher interested to digging deeper coping strategy of woman who has become a housewife and choose to work. Because of explanation above would we see how the responsibility themselves who they had to bear. Then appeared a question, how do they can a life that two the role of heavy. Aafter research held, researcher had some fact that woman employed having various problems and way it diverse.